2019
DOI: 10.1371/journal.pone.0226097
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of retinal structure and function in retinitis pigmentosa by co-registering microperimetry and optical coherence tomography

Abstract: PurposeTo evaluate the retinal structure-function relationships in the macula of retinitis pigmentosa (RP) patients by comparing microperimetry-3 (MP-3) images with co-registered optical coherence tomography (OCT) images.MethodsThirty patients with typical RP were recruited from our hospital. The maculae of patients were examined with MP-3 and OCT. The retinal sensitivity was measured by MP-3 at 40 testing points arranged concentrically in a 16° diameter of the central retina, and we divided the 40 points into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Point-to-point analysis revealed that greater retinal sensitivity was associated with the area of and within the hyperAF ring. In line with previous reports [ 15 ], ORT was more strongly correlated with retinal sensitivity than TRT. The hyperAF ring area and the longest diameter of the hyperAF ring were positively correlated with mean retinal sensitivity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Point-to-point analysis revealed that greater retinal sensitivity was associated with the area of and within the hyperAF ring. In line with previous reports [ 15 ], ORT was more strongly correlated with retinal sensitivity than TRT. The hyperAF ring area and the longest diameter of the hyperAF ring were positively correlated with mean retinal sensitivity.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding retinal thickness and retinal sensitivity, we observed that ORT was more strongly correlated with retinal sensitivity than TRT. Funatsu et al [ 15 ] investigated the retinal structure-function relationship in patients with RP by comparing microperimetry-3 images with co-registered OCT images. They showed that ORT was more strongly correlated with retinal sensitivity than TRT and suggested that these results may be due to photoreceptor cells being primarily injured in RP and that TRT can be affected by the thickness of the inner layers, which varies depending on the distance from the fovea and can be affected by the presence of an epiretinal membrane and degenerative thickening [ 15 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside zone 2 (3°–8°), a study by Konieczka et al found a reduction in mfERG responses corresponding to the reduction in the central retinal layer thickness [ 56 ]. Funatsu et al [ 62 ] reported in RCD patients reduced central retinal sensitivity measured by microperimetry corresponding to reduced outer retinal thickness at 6°–8°. Several studies on fundus autofluorescense imaging in RCD patients have paid attention to increased annular hyperautofluorescence in the parafoveolar area (within 3.0° to 10.5°), which is supposed to indicate a metabolic abnormality [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these potential problems, relationships between the structure and function have been extensively investigated in order to utilize the objective and quantitative parameters obtained from spectral-domain optical coherence tomography (SD-OCT) to assess the central retinal sensitivity of patients with RP . Previously, among several quantitative parameters, the width of the inner segment ellipsoid zone (IS-EZ) [1,3,7,8,10,13,14,18,19,21,24] and thickness of the outer retinal layer [2,4,9,12,15,20,23] have been shown to be significantly correlated with the central visual sensitivity. However, in these quantitative analyses, the subjects should be restricted to patients with visual acuity better than a certain level or measurable structural changes for analyzing the correlation between structural parameters and the visual function [1,9,10,12,13,15,18,20,21].…”
Section: Introductionmentioning
confidence: 99%